1998
DOI: 10.1002/(sici)1096-8644(199804)105:4<539::aid-ajpa10>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved DNA extraction from ancient bones using silica‐based spin columns

Abstract: We describe a simple method for extracting polymerase chain reaction-amplifiable DNA from ancient bones without the use of organic solvents. Bone powders are digested with proteinase K, and the DNA is purified directly using silica-based spin columns (QIAquick3, QIAGEN). The efficiency of this protocol is demonstrated using human bone samples ranging in age from 15 to 5,000 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
195
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(198 citation statements)
references
References 1 publication
1
195
0
2
Order By: Relevance
“…Silica-based methods use a bindrelease mechanism which has been shown to eliminate some inhibitors during purification (Yang et al, 1998). In this kit the purification reagents are in single-sample, self-contained cartridges.…”
Section: Discussionmentioning
confidence: 99%
“…Silica-based methods use a bindrelease mechanism which has been shown to eliminate some inhibitors during purification (Yang et al, 1998). In this kit the purification reagents are in single-sample, self-contained cartridges.…”
Section: Discussionmentioning
confidence: 99%
“…These primers were designed to eliminate bias by amplifying all Botrytis species, including any Botrytis DNA present in the herbarium sample, instead of targeting individual species. The need to amplify short DNA fragments (200-350 bp) was likely due to the low concentration and poor condition of the DNA that is recovered from archival or herbarium tissue samples (Yang et al 1998). Rogers and Bendich (1985) reported that 400 bp was the average size of DNA extracted from herbarium specimens.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted using urea‐based extraction buffer combined with silica‐based spin column purification—MinElute PCR Purification Kit (Qiagen), according to the manufactures protocols (Malmström et al, 2009; Yang, Eng, Waye, Dudar, & Saunders, 1998). The obtained DNA extracts were used for preparation of blunt‐end Illumina genomic libraries (Meyer & Kircher, 2010).…”
Section: Methodsmentioning
confidence: 99%